2015
DOI: 10.1248/bpb.b14-00695
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Epithelial-Mesenchymal Transition and Down-Regulation of miR-200c and miR-141 in Oxaliplatin-Resistant Colorectal Cancer Cells

Abstract: Epithelial-mesenchymal transition (EMT) and changes in the expression of the microRNA-200 (miR-200) family were examined in the human colorectal cancer (CRC) cell line SW620 with acquired oxaliplatin (L-OHP) resistance. Two CRC cell lines, SW480, derived from primary CRC, and SW620, derived from lymph node metastasis, which were obtained from the same patient, were used in the present study. L-OHP-resistant SW620 cells were obtained by exposure to L-OHP for 155 d. The concentration of L-OHP was increased to 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 34 publications
5
42
0
1
Order By: Relevance
“…However, we previously reported that the invasion activity of SW620/OxR cells was higher than that of SW620 cells, 11) as also observed in the present study. These results suggest that the acquisition of L-OHP resistance may inhibit the incorporation of let-7a, let-7b, and let-7g into exosomes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, we previously reported that the invasion activity of SW620/OxR cells was higher than that of SW620 cells, 11) as also observed in the present study. These results suggest that the acquisition of L-OHP resistance may inhibit the incorporation of let-7a, let-7b, and let-7g into exosomes.…”
Section: Discussionsupporting
confidence: 88%
“…Cell Culture The human CRC cell lines SW480 (DS Pharmabiomedical, Osaka, Japan), SW620 (American Tissue Culture Collection, Manassas, VA, U.S.A.), and SW620/OxR developed from SW620 cells as previously reported 11) were maintained in Leibovitz 15 medium (Life Technologies Corp., Carlsbad, CA, U.S.A.) supplemented with 10% fetal bovine serum (Sigma-Aldrich, St. Louis, MO, U.S.A.), 100 U/mL penicillin, and 100 µg/mL streptomycin at 37°C with 100% air. SW620/OxR cells were maintained in the presence of 80 µM L-OHP and were cultured without L-OHP for 1 passage before experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the present study, we observed that expression of 10 miRNAs decreased significantly in the exosome derived from chemoresistance prostate cancer cells compared to their parental cells. Downregulated expression of miR-141 plays a role in selective resistance to L-OHP and epithelial-mesenchymal transition (EMT) in CRCs during repeated treatments with L-OHP (25). miR-429 were downregulated in drugresistant epithelial ovarian cancer tissues (26).…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Recent studies have reported that the EMT has been strongly associated with cancer cell stemness 7,8) and chemoresistance to anti-cancer drugs, [9][10][11][12] indicating that targeting EMT could be a good strategy to overcome cancer metastasis. Notably, transforming growth factor-β1 (TGF-β1) has been known to be a primary inducer of EMT both during developmental process and cancer progression.…”
mentioning
confidence: 99%